New frontiers in intracranial imaging with HF-OCT: Ex vivo human cerebrovasculature evaluation and in vivo intracranial arteries dynamic visualization - Anagnostakou, Vania; Epshtein, Mark; Peker, Ahmet; Puri, Ajit S.; Singh, Jasmeet; Ughi, Giovanni J.; Gounis, Matthew J. (Frontiers in Photonics, 2022)
Optical coherence tomography (OCT) technology is a well-established diagnostic tool in multiple fields of medicine. Intravascular OCT technology has been used for more than a decade for the clinical imaging of coronary arteries, however, its use for the imaging of the human cerebrovasculature has been delayed by the challenges posed by the elevated vascular tortuosity. A novel high-frequency OCT (HF-OCT) probe designed for neurovascular use was evaluated in tortuous, ex vivo, human intracranial anatomy and, using an in vivo canine model, for the dynamic imaging of intracranial arteries and the subarachnoid trabecula (SAT). Using four cadavers, we investigated HF-OCT probe navigation and imaging performances in human anterior arterial circulation (from the M4 segment to internal carotid artery), in the posterior arterial circulation (from the P4 segment to vertebrobasilar junction) and in a broad range of venous sinuses. HF-OCT was able to gain distal access through elevated tortuosity and generate high-quality imaging data depicting vessel morphology, the vessel wall pathology (e.g., atherosclerotic disease and dissecting lesions), and the subarachnoid trabecula (SAT). Using an in vivo canine model, the HF-OCT probe was used to record stationary dynamic data in multiple intracranial vascular locations. Data showed the motion of the arteries and the SAT, including collisions between vessels, membranes, and the interaction between the SAT and the blood vessels. HF-OCT data allowed for the quantification of the dynamics of the vessels and the SAT, including vessel lateral motion with respect to the parenchyma, and collisions between large and small arteries. Results showed that the HF-OCT probe can overcome delivery obstacles in tortuous cerebrovascular anatomy and provide high-quality and high-resolution imaging at multiple distal locations, including M4 and P4 segments of the anterior and posterior circulations. HF-OCT has the potential to facilitate a better understanding of fine anatomical details of the cerebrovascular and perivascular environment, neurovascular disease, and collect real time information about the dynamics of the subarachnoid space and arteries and become a valuable diagnostic tool.